A novel method for measuring surface free energy of highly wettable mineral powders. (30th December 2019) - Zhang, Derun; Luo, Rong
Highlights: Spreading pressure is identified as driving force for liquid rising into highly wettable powders. Generalized modified Washburn equation captures spreading wetting mechanism of probe liquid into highly wettable powders. Parabolic relationship between capillary test results and square root of apolar liquid surface tension is demonstrated. Approximately same surface free energy results from proposed method and a previous method are obtained. Abstract: This paper develops a novel method to measure the surface free energy for the highly wettable mineral powders by means of the capillary rise measurements. In this method, a generalized modified Washburn equation is first derived to capture the spreading wetting mechanism of the probe liquid into the mineral powders with high wettability. A series of apolar liquids are then selected to conduct the capillary rise test to generate a plot of the measured test results against the square root of the liquid surface tension. Fitting such a plot with a parabolic function, the resultant effective capillary radius and the powder apolar surface energy component can be solved. Then the spreading pressure of two independent liquids is calculated from their capillary rise test results. The polar acid and polar base surface energy components of the highly wettable powders can be finally determined by substituting the calculated spreading pressure values into the Good-van Oss-Chaudhury model. The proposed method has been successfully applied to measure the surface free energy for four typical types of mineral powders. The measured surface free energies of the selected powders are found to be approximately the same as those obtained from a previous method with different principle. In this regard, the proposed method is validated to be capable of accurately measuring the surface free energy for highly wettable mineral powders.